DIFFERENTIATED INSTRUCTION ON WRITING COMPETENCE AMONG GRADE XI STUDENTS: EXPLORATION OF STUDENTS’ PERCEPTIONS - Sri Utami; Yanuar Dwi Prastyo (STKIP PGRI Situbondo, 2026)
This study explores the impact of differentiated instruction on the writing proficiency of Grade XI students at SMA Al Azhar 3 Bandar Lampung. Employing a quasi-experimental design, 60 students were divided equally into experimental and control groups. The experimental group received tailored instruction based on students’ interests and learning profiles, while the control group followed conventional methods. Pre- and post-tests were administered, and data were analyzed using descriptive statistics, independent sample t-tests, and analysis of variance. Results revealed a significant improvement in the experimental group’s writing scores, with a mean gain of 28.67 points compared to 9.5 in the control group. Additionally, thematic analysis of student interviews, guided by Braun and Clarke’s framework, identified three key themes: positive impact on engagement and comprehension, advantages enhancing learning dynamics, and minimal barriers with significant benefits. Students found the method enjoyable, structured, and effective in supporting their learning. These findings suggest that differentiated instruction not only improves students’ academic outcomes but also fosters motivation and active participation. Theoretically, the study supports learner-centered instructional models, while practically, it offers insights for educators seeking more inclusive and effective strategies. Despite limitations related to sample size and context, the research provides a strong case for broader implementation and further exploration of differentiated instruction in varied educational settings.